An attempt at estimation of environmental components of phenotypical variance of human motor characteristics - Swornowski, Piotr (Anthropological Review, 1984)
The paper presents an attempt at estimation of the size of environmentally induced parts. of a total phenotypical variance of human motoric characteristics: isometric strength, flexibility, velocity in 10 m dash, standing high jump, reaction time to an acoustic stimulus and general efficiency. The group examined consisted of 41 males, students of physical education who repeated relevant tests several times each. During analysis of the data fluctuating variance (VEs+ VEr) and coefficient of replicability (being a maximum estimate of heritability — h2) were determined Furthermore values of measures of genetic polymorphism (Pg) and ecosensitivity (De,s+r) Were determined. Obtained results allow to conclude that human motoric characteristics are mostly determined, with respect to their variabllity, by variability of genetic endowment while environmentally Induced processes of adaptability and adjustment are less important for determining their total variability.